Fichte and Transcendental Philosophy
X, 349 p.
Keywords: With renewed attention to German idealism in general and to Fichte in particular, this timely collection of new papers will be of interest to anyone concerned with transcendental philosophy, German idealism, modern German philosophy and transcendental arguments.